2014
DOI: 10.5296/ijl.v6i4.6114
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cooperative Learning in Enhancing Speaking Skills and Attitudes towards Learning English

Abstract: This study investigates the effectiveness of cooperative learning in English language classrooms to enhance Yemeni students' speaking skills and attitudes. A quasi-experimental interrupted time series design was used with sixty undergraduates enrolled in the foundation English programme at Hadhramout University, Yemen. The data of the current study were gathered at multiple points of time before and after the end of the experiment to determine the effectiveness of cooperative learning on the sample's speaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…In terms of practical implications, the teacher-centred teaching approach does not help the students to participate and improve their experience in order to overcome the feeling of anxiety inside the classroom as the students tend be passive participants most of the time (Bose 2002, Al-Tamimi & Attamimi 2014. Teachers can try different teaching methods which will make the process of learning student-centred.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of practical implications, the teacher-centred teaching approach does not help the students to participate and improve their experience in order to overcome the feeling of anxiety inside the classroom as the students tend be passive participants most of the time (Bose 2002, Al-Tamimi & Attamimi 2014. Teachers can try different teaching methods which will make the process of learning student-centred.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that, though students have a strong internal motivation to learn English as a second language (Attamimi & Abdul Rahim, 2011), there remain several inherent conditions, ranging from tribal to religious and linguistic identities, that will instigate conflict with their concurrent use and practice to make English as a target language to master. This observation can be most clearly corroborated when these students are observed in their attempts to speak English (Al-Tamimi & Attamimi, 2014, 2018. In most cases, any semblance of non-verbal awareness in the act of speaking English appears to be non-existent.…”
Section: Statement Of the Problemmentioning
confidence: 59%
“…Thirdly, it can be proved that CL strategies promote positive attitudes in students when using the target language verbally. It can be evidenced in the studies carried out by Nasser (2014) and Ahmed and Bedri (2017) where the results showed an increase concerning students' positive attitudes in relation to their motivation to use the language during oral communication.…”
Section: Discussionmentioning
confidence: 87%
“…Researches in different countries have demonstrated that CL is effective to develop students' English skills, mainly speaking. Nasser (2014), conducted a study to highlight the effectiveness of CL strategies on the undergraduate learners. The study results showed a remarkable development in their speaking skills as well as improvement in their attitudes towards EFL learning.…”
Section: The Relationship Between CL and The Development Of The Speakmentioning
confidence: 99%